Rhizophlyctis Rosea (Rhizophlyctidales, Chytridiomycota) in soil: Frequency, abundance and density of colonization of lens paper baits - Marano, Agostina Virginia (2011)
The distribution of Rhizophlyctis rosea was examined in soils from 22 locations including disturbed and undisturbed habitats in eastern Australia. Thalli of Rh. rosea were observed on baits from 60% of the sites (67% agricultural and 33% natural soils). Within the disturbed habitats, samples from four sites that experience different temperature ranges were assessed for frequency, abundance, number of thalli and density of colonization of the baits. Lens paper baits were placed into Petri dishes with sterile deionized water and air-dried soil and incubated for up to four days at 20, 35 or 40°C, and at 20°C after freezing (-15°C) and heating (80°C) the soil. The abundance, frequency, number of thalli and density of colonization varied among the samples analysed, with the greatest abundance, number of thalli and density for Pitt Town Bottoms and the highest frequency for Pitt Town Bottoms and Narrabri soils. All isolates grew and released zoospores after heat and freezing treatments. Freezing soil before baiting increased the number of thalli and density of colonization of baits, while heating decreased the frequency and abundance of Rh. rosea.